Perbedaan Tingkat Kecemasan antara Pasien Diabetes Melitus Tipe 2 Disertai Komplikasi dengan Tanpa Komplikasi di RSUD Dr. Moewardi - Anggarani, Nia; Nugroho, IGB Indro; Setyawan, Sigit (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Diabetes mellitus (DM) is referred to as growing epidemic. The prevalence of type 2 diabetes mellitus in Indonesia is 18.6% in urban areas and 9.2% in rural areas. It is estimated that in 2030 the prevalence of DM in Indonesia reached 21.3 million people. Chronic diseases such as diabetes mellitus are associated with the emergence of anxiety disorders. It has been reported that anxiety disorders associated with age, gender, occupation and complications of diabetes mellitus. In addition, an increase in the symptoms of anxiety disorder related to the number and the type of complications suffered by patients with diabetes mellitus. This study aimed to analyze the differences of anxiety level in type 2 diabetes mellitus patients with and without complications in Dr. Moewardi Hospital. Method: 91 type 2 diabetes mellitus patients of Internal Medicine Clinic Dr. Moewardi Hospital participated in a cross-sectional study. 40 patients with complications and 51 patients without complications were recruited with non-probability sampling methods, which was consecutive sampling. Each respondent was given a standard TMAS (Taylor Manifest Anxiety Scale) questionnaire and LMMPI (Lie-scale Minnesota Multiphasic Personality Inventory) questionnaire. The TMAS questionnaire contains 50 questions, which has